Reseña de «The Mummy Under the Bed. Essays on Gender and Methodology in the Ancient Near East» - Patricia Bou Pérez (Asparkía)
Reseña del volumen The Mummy Under the Bed. Essays on Gender and Methodology in the Ancient Near East, editado por Katrien De Graef, Agnès Garcia-Ventura, Anne Goddeeris y Beth Alpert Nakhai.